Self-Unfolding of the Phenomenon of Hryhorii Skovoroda - Boichenko, M. I. (Anthropological Measurements of Philosophical Research, 2022)
Purpose. This article provides a morphological study of the life of Hryhorii Skovoroda as a philosopher’s self-construction – compared to the lives of such philosophers as Immanuel Kant, Friedrich Nietzsche, Martin Heidegger and Henry Thoreau. Theoretical basis. The study is based on the use of a monadological approach to history in combination with the biographical method. The ideas of the classical philosophical systems of Gottfried Leibniz and Oswald Spengler are applied taking into account their rethinking by Ukrainian philosophers Ivan Boichenko and Vadym Menzhulin. Thanks to this, the life of the Ukrainian philosopher Hryhorii Skovoroda is considered as a monad that constantly carries out its own semantic self-unfolding. Originality. The thorough paradoxical nature of Hryhorii Skovoroda’s philosophy, which is attributed to him based on other philosophical systems, is completely removed by the performative sequence of his life as a philosopher, which is shown by systematic comparisons of the main characteristics of his life with the lives of other prominent philosophers who subordinated their actions to their philosophical concept. Conclusions. Hryhorii Skovoroda’s philosophy is a monad, that is, such a primary phenomenon that cannot be explained from other phenomena: comparison with other monads is only a pretext for identifying the characteristics of the monad under study, which are gradually revealed as a manifestation of its originality and uniqueness. The originality of the philosophical conceptualization of Skovoroda’s life should be carried out in a step-by-step comparison with the conscious life of other philosophers, and such a comparison needs to be continued, constantly carried out. The peculiarity of this study is an attempt to provide a methodological justification for such a comparative morphological-biographical philosophical research.